Self-Assembly of Multinuclear Sandwich Silver(I) Complexes by Cooperation of Hexakis(azaheteroaryl)benzene Ligands, Argentophilic Interactions, and Fluoride Inclusion - Drev, Miha (Inorg Chem, 2020)
[Image: see text] Self-assembly of AgOTf and AgF with the hexatopic ligands hexakis(pyridin-2-yl)benzene (2) and 2,4,6-tris(pyridin-2-yl)-1,3,5-tris(quinolin-2-yl)benzene (3) affords the discrete sandwich-shaped complexes [Ag(4)F(2)(2)](OTf)(3), [Ag(4)F(3)(2)](OTf)(3), and [Ag(5)F(2)(2)](OTf)(4). The solid-state structures of the complexes were characterized by single-crystal X-ray diffraction analysis, which revealed that the fluoride anion is coordinated in the center of the Ag(4)-square or Ag(5)-pentagon units which are positioned between two molecules of the hexakis(azaheteroaryl)benzene. The generation of complexes is dictated by a unique cooperation of ligand coordination, argentophilicity, and fluoride anion inclusion. All three complexes adopt highly symmetrical structures in solution, as evidenced by appearance of one set of proton resonances for the two ligands arranged face to face.